2017
DOI: 10.1093/jamia/ocx100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of computerized decision support system implementations on patient outcomes in inpatient care: a systematic review

Abstract: Most of the included CDSS studies were associated with positive patient outcomes effects but with substantial differences regarding the clinical impact. A subset of 6 disease entities could be filtered in which CDSS should be given special consideration at sites where computer-assisted decision-making is deemed to be underutilized. Registration number on PROSPERO: CRD42016049946.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 61 publications
1
98
1
3
Order By: Relevance
“…These investigators nonetheless found limited evidence for improved clinical outcomes, cost containment or operational efficiency. 26 A more recent review of inpatient care by Varghese, et al, 28 describes highly variable effects with 70% of studies reporting some improvement in patient outcomes, and more substantial prevention of harm only for select disease entities.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators nonetheless found limited evidence for improved clinical outcomes, cost containment or operational efficiency. 26 A more recent review of inpatient care by Varghese, et al, 28 describes highly variable effects with 70% of studies reporting some improvement in patient outcomes, and more substantial prevention of harm only for select disease entities.…”
Section: Discussionmentioning
confidence: 99%
“…The [4] indicates that decision support systems have significantly improved clinical practice in 68% of tests. Varghese J. et al in the [5] cites data based on the results of 70 studies, which confirm that the use of the clinical decision support system in 23% of cases showed a significant positive effect, in 29%an average positive effect, while in 29% of cases, the applied technologies showed none or little effect on the overall health of the patients. Market Research Future (MRFR) states that the market for clinical decision support systems will expand due to a steady compound annual growth rate (CAGR) during the period from 2018 to 2023 as the result of increasing demand for data management technologies [6].…”
Section: Introductionmentioning
confidence: 87%
“…About decision making processes, a general definition of clinical decision support systems is currently lacking. Even if the reference goes to Kawamoto et al (10), the reason of the difficulty in defining CDSS relies in their nature of sociotechnical systems (11). Among the various CDSS characteristics, two are especially seen as necessary: (a) Leverage of disease knowledge from which to formulate risk predictions (b) Integration between relevant stakeholders at hospital site.…”
Section: Translational Potentialmentioning
confidence: 99%